To convert the equation \( y = 2(x - 5)^2 - 10 \) to standard form, we need to expand the expression.
-
Start with the equation: \[ y = 2(x - 5)^2 - 10 \]
-
Expand \((x - 5)^2\): \[ (x - 5)^2 = x^2 - 10x + 25 \]
-
Substitute back into the equation: \[ y = 2(x^2 - 10x + 25) - 10 \]
-
Distribute the 2: \[ y = 2x^2 - 20x + 50 - 10 \]
-
Combine like terms: \[ y = 2x^2 - 20x + 40 \]
Now the equation is in standard form \( y = ax^2 + bx + c \), where \( a = 2 \), \( b = -20 \), and \( c = 40 \).
Thus, the standard form of the equation is: \[ y = 2x^2 - 20x + 40 \]